2021
DOI: 10.32915/pleiade.v15i33.699
|View full text |Cite
|
Sign up to set email alerts
|

Estado Nutricional e Variáveis Associadas de Crianças de 0 a 5 anos de Centros de Educação Infantil de Município de Fronteira Internacional: Estudo Ecológico

Abstract: Esta pesquisa teve como objetivo analisar o estado nutricional das crianças de 0 a 5 anos de idade de Centros de Educação Infantil de Foz do Iguaçu-PR, e identificar as variáveis associadas utilizando-se de abordagem espacial. Estudo ecológico, descritivo e transversal, com dados obtidos do banco de dados do Sistema de Vigilância Alimentar e Nutricional. As variáveis dependentes utilizadas foram: percentual de magreza, eutrofia, risco de sobrepeso e obesidade. As variáveis independentes foram: sexo, idade e va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…A survey analyzed the nutritional status of children from 0 to 5 years of age in 5 health districts of Foz do Iguaçu-PR, and found that 4.3% of them were thin, 62.8% eutrophic, 20.2% risk of overweight and 12.7% obesity [32]. In this sense, about 37.2% of these individuals were outside the normal range, a worrying fact when considering that 32.7% were above the ideal parameter and 4.3% were below it, evidencing serious epidemiological problems linked to the lack of public policies for the less favored.…”
Section: Historical Series Of Bmi For Agementioning
confidence: 99%
“…A survey analyzed the nutritional status of children from 0 to 5 years of age in 5 health districts of Foz do Iguaçu-PR, and found that 4.3% of them were thin, 62.8% eutrophic, 20.2% risk of overweight and 12.7% obesity [32]. In this sense, about 37.2% of these individuals were outside the normal range, a worrying fact when considering that 32.7% were above the ideal parameter and 4.3% were below it, evidencing serious epidemiological problems linked to the lack of public policies for the less favored.…”
Section: Historical Series Of Bmi For Agementioning
confidence: 99%